Alleviating water scarcity in Northern China balancing options and policies among Chinese decision-makers - Lasserre, F (Water science and technology : a journal of the International Association on Water Pollution Research, 2003)
Water scarcity is mostly a man-made problem that increasingly affects people's lives and questions economic output in Northern China. Policy options addressing the serious water shortages in the region include conservation and water management reform, which is unpopular; grain imports and the downsizing of agriculture; derivation of Yangze water; derivation of the Amur and other international rivers. All solutions present major difficulties, whether domestic or international, for the Chinese authorities. While major decisions have not yet been taken, evidence shows major works such as water transfers from the Yangze or water pricing are not only unavoidable, but will not be enough to meet the growing demand for water in the region